Melewati Tantangan Masa Sulit: Peran Gereja dan Pendampingan Rohani dalam Navigasi Quarter Life Crisis - Herman, Samuel; Trifosa, Florence (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2025)
This study aims to analyze the role of the church in addressing the quarter-life crisis through pastoral counseling, highlighting Jesus’ teachings as a model of selfless service in providing spiritual and psychological support to young individuals transitioning into adulthood. This study employs a qualitative approach with literature review as the primary method. Analysis is conducted using biblical hermeneutics to understand the concept of anxiety from a biblical perspective and its relevance to young individuals' mental and spiritual well-being. The study finds that anxiety is a central element in the quarter-life crisis, affecting mental and physical health. Pastoral counseling offers a holistic approach encompassing spiritual, emotional, and psychological support. The church, through pastors as shepherds, provides guidance rooted in biblical teachings to help individuals navigate this crisis. The church plays a crucial role in offering pastoral counseling as a response to the quarter-life crisis. By emphasizing the Word of God as a guiding principle, the church helps individuals overcome anxiety through confession, obedience to God, and prayer. Structured counseling enables a more comprehensive recovery for those transitioning into adulthood.